2015
DOI: 10.1152/ajpendo.00494.2014
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergically stimulated blood flow in brown adipose tissue is not dependent on thermogenesis

Abstract: Brown adipose tissue (BAT) thermogenesis relies on blood flow to be supplied with nutrients and oxygen and for the distribution of the generated heat to the rest of the body. Therefore, it is fundamental to understand the mechanisms by which blood flow is regulated and its relation to thermogenesis. Here, we present high-resolution laser-Doppler imaging (HR-LDR) as a novel method for noninvasive in vivo measurement of BAT blood flow in mice. Using HR-LDR, we found that norepinephrine stimulation increases BAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 35 publications
(39 reference statements)
1
36
0
1
Order By: Relevance
“…In human PET imaging studies, brown adipose tissue (BAT) 18 F-FDG uptake has been shown to be markedly increased by controlled cold exposure (1,2) and agonism of b3 adrenergic receptors (3), correlating positively with changes in energy expenditure (1,3). Similar findings have been made in small-animal PET imaging studies performed on mice (4,5).…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…In human PET imaging studies, brown adipose tissue (BAT) 18 F-FDG uptake has been shown to be markedly increased by controlled cold exposure (1,2) and agonism of b3 adrenergic receptors (3), correlating positively with changes in energy expenditure (1,3). Similar findings have been made in small-animal PET imaging studies performed on mice (4,5).…”
mentioning
confidence: 63%
“…Both WT and UCP1 KO mice showed an increased mean SUV for 18 F-FDG in BAT in response to CL 316, 243 treatment relative to vehicle treatment (P , 0.0001) (Fig. 3B), with no significant effect of genotype found (F 1, 14 5 0.17, P 5 0.68).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These observations suggest that an important function of BAT innervation might be the redistribution of core heat to critical regions in the supraclavicular and spinal regions. In this regard, norepinephrine infusion was recently shown to dramatically increase blood flow to murine BAT in the absence of UCP1-mediated thermogenesis (42).…”
Section: Relationship Between Blood Flow and 18 F-fdg Uptakementioning
confidence: 99%